THE GLASS HOTEL - Mandel, Emily St. John, 1979- (New York : Random House Large Print, 2020)
Vincent is a bartender at the Hotel Caiette, a five-star lodging on the northernmost tip of Vancouver Island. On the night she meets Jonathan Alkaitis, a hooded figure scrawls a message on the lobby s glass wall: Why don t you swallow broken glass. High above Manhattan, a greater crime is committed: Alkaitis is running an international Ponzi scheme, moving imaginary sums of money through clients accounts. When the financial empire collapses, it obliterates countless fortunes and devastates lives. Vincent, who had been posing as Jonathan s wife, walks away into the night. Years later, a victim of the fraud is hired to investigate a strange occurrence: a woman has seemingly vanished from the deck of a container ship between ports of call.
Keywords: Missing persons -- Fiction; Ponzi schemes -- New York (State) -- Fiction; Detective and mystery fiction